Isolation and identification of lactic acid bacteria from abalone (Haliotis asinina) as a potential candidate of probiotic - SARKONO SARKONO; FATURRAHMAN FATURRAHMAN; YAYAN SOFYAN (Smujo International, 2010)
Abstract. Sarkono, Faturrahman, Sofyan Y. 2010. Isolation and identification of lactic acid bacteria from abalone (Haliotis asinina) as a potential candidate of probiotic. Nusantara Bioscience 2: 38-42. The purpose of this study was to isolate, select and characterize lactic acid bacteria (LAB) from abalone as a potential candidate probiotic in abalone cultivation system. Selective isolation of LAB performed using de Man Rogosa Sharpe medium. LAB isolate that potential as probiotics were screened. Selection was based on its ability to suppress the growth of pathogenic bacteria, bacterial resistance to acidic conditions and bacterial resistance to bile salts (bile). Further characterization and identification conducted to determine the species. The results showed that two of the ten isolates potential to be developed as probiotic bacteria that have the ability to inhibit several pathogenic bacteria such as Escherichia coli, Bacillus cereus dan Staphylococcus aureus, able to grow at acidic condition and bile tolerance during the incubation for 24 hours. Based on the API test kit, both isolate identified as members of the species Lactobacillus paracasei ssp. paracasei.